The Relationship Between Learning Facilities and Learning Motivation in Social Education Science Subjects Citizens Learn Package B at PKBM Insan Cendikia in Padang City - Pertiwi, Fauziah; Syur'aini, Syur'aini (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2024)
This research is motivated by the less than optimal use of learning facilities that support learning, especially in social education subjects. The aim of this research activity is to find out: an overview of the learning facilities and learning motivation of residents studying Package B at PKBM Insan Cendekia, as well as the relationship between learning facilities and the motivation to study social studies subjects of residents studying Package B at PKBM Insan Cendikia. The research approach is quantitative with a correlational type. The population in this study was 41 people studying Package B, PKBM Insan Cendikia. The sample for this study was 80% of the total population taken using the technique of stratified random sampling, namely 32 study residents. Data was collected using an instrument in the form of a questionnaire. Data analysis techniques use percentage and product moment formulas. Research results: (1) learning facilities are categorized as quite good; (2) motivation for learning social studies subjects is categorized as moderate; (3) there is a very significant relationship between learning facilities and motivation to study social studies subjects of residents studying package B PKBM Insan Cendikia in Padang City.